A new subspecies of Anolis porcatus (Sauria: Polychrotidae) from Western Cuba - Pérez-Beato, O (1996)
A new subspecies of Anolis porcatus Gray, is described from westem Cuba. The main characters differentiating Anolis porcattis aracelyae are a Iight blúe tint dorsum and an elongated ear opening. The distribution of the new taxon may be explained on the basis of allopatry in the Guaniguanico mountain range